Nerve Tumors: What the MSK Radiologist Should Know - Tagliafico, Alberto Stefano; Isaac, Amanda; Bignotti, Bianca; Rossi, Federica; Zaottini, Federico; Martinoli, Carlo (Seminars in Musculoskeletal Radiology, 2019)
Nerve tumors are rare and heterogeneous soft tissue tumors arising from a peripheral nerve or showing nerve sheath differentiation. In a radiologic setting it is necessary to recognize soft tissue lesions that are of neural origin, their association with a peripheral nerve, and whether they are a true tumor or a so-called pseudotumor such as a neuroma, fibrolipoma, or peripheral nerve sheath ganglion. Ultrasound (US) and magnetic resonance imaging are the best modalities to characterize these lesions. US can be used to guide biopsy in difficult and uncertain cases when the lesion is either indeterminate or possibly malignant. At present, no single imaging feature or reproducible criteria, or a combination, can differentiate reliably between a neurofibroma and a schwannoma or discriminate with certainty between benign and malignant neurogenic tumors. Adequate imaging and consultation with a nerve tumors/sarcoma unit is advised.
Keywords: peripheral nerves; tumors; sarcoma; ultrasound; magnetic resonance imaging